Diarrhea as a Presenting Symptom of Disseminated Toxoplasmosis - Matthew Glover; Zhouwen Tang; Robert Sealock; Shilpa Jain (Case Reports in Gastrointestinal Medicine)
Disseminated toxoplasmosis is uncommon in both immunocompetent and immunocompromised hosts with gastrointestinal involvement being rarely described. We report a case of disseminated gastrointestinal toxoplasmosis in an immunocompromised man who presented with one month of diarrhea and abdominal pain. Imaging showed thickening of the ascending colon and cecum. Esophagogastroduodenoscopy and colonoscopy biopsies revealed Toxoplasma gondii, confirmed by immunostain. Symptoms completely resolved following treatment with pyrimethamine, sulfadiazine, and leucovorin. This case highlights the importance of including toxoplasmosis in the differential diagnosis of any immunocompromised individual presenting with gastrointestinal symptoms.